2008
DOI: 10.1128/jvi.01028-08
|View full text |Cite
|
Sign up to set email alerts
|

Coxsackievirus B4 Uses Autophagy for Replication after Calpain Activation in Rat Primary Neurons

Abstract: Coxsackievirus is the most important cause of meningitis and encephalitis in infants; an infection is sometimes fatal or may lead to neurodevelopmental defects. Here, we show that coxsackievirus B4 (CVB4) induces an autophagy pathway for replication in rat primary neurons. Notably, calpain inhibitors reduce autophagosome formation. Conversely, the inhibition of the autophagy pathway with 3-methyladenine inhibits calpain activation. This work reveals, for the first time, that calpain is essential for the autoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
87
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(89 citation statements)
references
References 12 publications
2
87
0
Order By: Relevance
“…Some pathogens induce early stages of autophagy but block later stages (i.e., autophagolysosomal fusion) (28,75,81,88,95), so we investigated whether HBV could induce a complete autophagic process (i.e., autophagic flux) by measuring the level of the autophagic substrate p62, an adaptor protein that interacts with LC3 and is specifically degraded by the autophagy pathway (4,59). The results showed that HBV could not change the expression of p62, in contrast to rapamycin ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some pathogens induce early stages of autophagy but block later stages (i.e., autophagolysosomal fusion) (28,75,81,88,95), so we investigated whether HBV could induce a complete autophagic process (i.e., autophagic flux) by measuring the level of the autophagic substrate p62, an adaptor protein that interacts with LC3 and is specifically degraded by the autophagy pathway (4,59). The results showed that HBV could not change the expression of p62, in contrast to rapamycin ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy can contribute to innate and adaptive immunity against intracellular microbial pathogens (11, 43). However, this intracellular process has been exploited by some viruses to benefit their replication, such as poliovirus, coxsackievirus, dengue virus, hepatitis C virus, human immunodeficiency virus, and influenza A virus (14,28,42,44,75,80,95,100).…”
mentioning
confidence: 99%
“…Infection by poliovirus stimulates LC3 activation and autophagosome formation by a mechanism that involves the direct effects of viral nonstructural proteins (16,37); inhibition of autophagy interferes with poliovirus replication and replication of other enteroviruses in vitro (16,(38)(39)(40), and autophagy is involved in the pathogenesis of coxsackievirus-induced pancreatitis in vivo (41). Another picornavirus, foot-and-mouth disease virus (FMDV), stimulates autophagosome formation early in infection, before viral nonstructural proteins are synthesized, and FMDV colocalizes with LC3, presumably in autophagosomes, within 2 h of infection (42).…”
Section: Discussionmentioning
confidence: 99%
“…It has been hypothesized that this is achieved by increasing a protein-activated signaling cascade, known as the calpain-dependent pathway [45] .…”
Section: Pathogen Adaptations To Host Cell Autophagymentioning
confidence: 99%